2006
DOI: 10.1016/j.neulet.2006.06.061
|View full text |Cite
|
Sign up to set email alerts
|

The role of tissue transglutaminase in 1-methyl-4-phenylpyridinium (MPP+)-induced toxicity in differentiated human SH-SY5Y neuroblastoma cells

Abstract: Tissue transglutaminase (TG2) can induce post-translational modification of proteins, resulting in protein cross-linking or incorporation of polyamines into substrates, and can also function as a signal transducing G protein. The role of TG2 in the formation of insoluble cross-links has led to its implication in some neurodegenerative conditions. Exposure of pre-differentiated SH-SY5Y cells to the Parkinsonian neurotoxin 1-methyl-4-phenylpyridinium ion (MPP + ) resulted in significant dose-dependent reductions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Therefore, we treated the cells with the mitochondrial complex I inhibitor MPP + , an active metabolite of 1-methyl-4-phenyl-1,2,3,6 tetrahydropyridine (MPTP) that is commonly used as a toxin to induce PD-like phenomena in several well-established cellular and in vivo PD models (Burns et al, 1983;Heikkila et al, 1984). In line with previous work by Beck et al (2006), we found that incubation with MPP + (1-5 mM) for 24 h induced a concentration-dependent activation of tTG activity in RA-differentiated WT SH-SY5Y cells (Fig. 5A).…”
Section: Ttg-dependent A-synuclein Transamidation Is Induced By the Psupporting
confidence: 66%
See 2 more Smart Citations
“…Therefore, we treated the cells with the mitochondrial complex I inhibitor MPP + , an active metabolite of 1-methyl-4-phenyl-1,2,3,6 tetrahydropyridine (MPTP) that is commonly used as a toxin to induce PD-like phenomena in several well-established cellular and in vivo PD models (Burns et al, 1983;Heikkila et al, 1984). In line with previous work by Beck et al (2006), we found that incubation with MPP + (1-5 mM) for 24 h induced a concentration-dependent activation of tTG activity in RA-differentiated WT SH-SY5Y cells (Fig. 5A).…”
Section: Ttg-dependent A-synuclein Transamidation Is Induced By the Psupporting
confidence: 66%
“…2A) In contrast to the in vitro data, the results from our cellular model clearly distinguished between the different drugs on both potency and efficacy of tTG inhibition. In fact, to our knowledge, our data are among the first to establish a clear concentrationeffect relationship of pharmacologic tTG inhibition in cells, although using a different experimental setup, effects of inhibitors on tTG activity in SH-SY5Y cells have been reported previously (Beck et al, 2006;Lesort et al, 2003;Singh et al, 2003). This model, originally characterized by Zhang et al (1998), is based on detection of tTG-mediated covalent incorporation of the amine donor BAP into cellular proteins following activation of transamidation activity by a rise in intracellular Ca 2+ concentration as a result of exposure of the cells to Ca 2+ ionophores like A23187.…”
Section: In Vitro and Cellular Inhibition Of Ttg Activitymentioning
confidence: 54%
See 1 more Smart Citation
“…Total TG activity was determined using a method developed by Beck et al [12] with modifications. BV-2 cells (8 × 10 5 cells/dish) were plated onto non-coating 35-mm dishes and stimulated with 300 ng/ml LPS for 24 h in the presence of 250 µ M biotinylated pentylamine (Thermo Fisher Scientific, Waltham, Mass., USA) as the substrate for TG enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported the association between TGs and neurodegeneration [41][42][43]. On the other hand, microglial phagocytosis has been reported to be involved in neuronal death in neurodegenerative diseases [44,45].…”
Section: Phagocytosis In Neurodegenerative Diseasesmentioning
confidence: 99%